Glucagon-like peptide 1-related peptides increase nitric oxide effects to reduce platelet activation - Barale, Cristina; Buracco, Simona; Cavalot, Franco; Frascaroli, Chiara; Guerrasio, Angelo; Russo, Isabella (Thrombosis and Haemostasis, 2017)
Glucagon-like peptide 1 (GLP-1) is object of intensive investigation for not only its metabolic effects but also the protective vascular actions. Since platelets exert a primary role in the pathogenesis of atherosclerosis, inflammation and vascular complications, we investigated whether GLP-1 directly influences platelet reactivity. For this purpose, in platelets from 72 healthy volunteers we evaluated GLP-1 receptor (GLP-1R) expression and the effects of a 15-minute incubation with the native form GLP-1(7–36), the N-terminally truncated form GLP-1(9–36) and the GLP-1 analogue Liraglutide (100 nmol/l) on: i) aggregation induced by collagen or arachidonic acid (AA); ii) platelet function under shear stress; iii) cGMP and cAMP synthesis and cGMP-dependent protein kinase (PKG)-induced Vasodilator-Stimulated-Phosphoprotein (VASP) phosphorylation; iv) activation of the signalling molecules Phosphatidylinositol 3-Kinase (PI3-K)/Akt and Mitogen Activated Protein Kinase (MAPK)/ERK-1/2; and v) oxidative stress. Experiments were repeated in the presence of the nitric oxide donor Na–nitroprusside. We found that platelets constitutively express GLP-1R and that, independently of GLP-1R, GLP-1(7–36), GLP-1(9–36) and Liraglutide exert platelet inhibitory effects as shown by: a) increased NO-antiaggregating effects, b) increased the activation of the cGMP/PKG/VASP pathway, c) reduced the activation of PI3-K/Akt and MAPK/ERK-2 pathways, d) reduced the AA-induced oxidative stress. When the experiments were repeated in the presence of the antagonist of GLP-1R Exendin(9–39), the platelet inhibitory effects were maintained, thus indicating a mechanism independent of GLP-1R. In conclusion, GLP-1(7–36), its degradation product GLP-1(9–36) and Liraglutide exert similar inhibitory effects on platelet activation, suggesting a potential protective effect on the cardiovascular system.
Keywords: Platelets; glucagone-like peptide 1; Liraglutide; nitric oxide; diabetes